A novel Pickering emulsion stabilized by rational designed agar microsphere. (1st May 2023) - Chen, Zizhou; Xu, Yanhong; Xiao, Zhechen; Zhang, Yonghui; Weng, Huifen; Yang, Qiuming; Xiao, Qiong; Xiao, Anfeng
Abstract: An agar microsphere model was established to explore the structure-surface activity relationship between the surface structure of soft solid particles and the stability of emulsion. Mechanical stirring emulsification method was firstly optimized to produce micron-sized agar microspheres (AMs, ≤10 μm). The surface wettability and surface charge of agar microspheres were regulated by octenyl succinylation. The contact angles of the AMs were significantly increased from 54.75° to 101.78° after octenyl succinylation, and zeta potential changed from −27.73 mV to −45.5 mV. Moreover, the Pickering stabilizers were successfully prepared by using octenyl succinylated agar microspheres (OSAMs) as Pickering emulsifier through one-step shearing. Confocal laser scanning microscopy revealed the OSAMs adsorbed onto the interface as multilayer aggregates or monolayer bridging structures to form a 3D network structure to stabilize the emulsion. The emulsion stability was sensitive to electrostatic repulsion of surface charges and electrostatic shielding of salt ions, but not responsive to temperature. This study could be useful in the design and development of gelling polysaccharide-based Pickering stabilizers, and provide potential applications in the food and pharmaceutical industries. Graphical abstract: Image 1 Highlights: Micron-sized agar microspheres with good surface wettability are designed. Particles stabilize emulsion by forming monolayer/multilayer structure at the interface. Pickering emulsion structure is regulated by oil fraction and particles composition. The Pickering emulsions are resistant to temperature but not salt ions and pH.